THE RELATIONSHIP BETWEEN SPORT EDUCATION MODEL AND MOTIVATION TOWARDS PHYSICAL EDUCATION LEARNING OUTCOMES - Herna Hermansyah, Herna Hermansyah; akhmad Sobarna; Muchamad Ishak (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
The purpose of this study was to determine whether there is a relationship between the sport education model and motivation on the learning outcomes of Physical Education. This study used correlational research. The population of all students of Cijaralang 2 Elementary School with a total of 180 students consisting of grades I to VI, the sampling technique used Cluster Random sampling, and the research sample was 51 students of grade V of Cijaralang 2 Elementary School. The research instruments used in this study were questionnaires to measure the sport education model, questionnaires to measure motivation and documentation to measure physical education learning outcomes. Research Results There is a positive and significant relationship between the Sport Education Model and motivation on the learning outcomes of physical education students of Cijaralang 2 Elementary School, this is indicated by the calculated F value> F table (228.753> 2.37) and a sig value of 0.000 <0.05. While the correlation value is 0.895. This relationship can be interpreted that the better the sport education model and motivation possessed by students, the higher the chances of students getting optimal physical education learning outcomes.